Analisis Kerusakan Akibat Hama dan Penyakit pada Tegakan Balangeran (Shorea balangeran (Korth.) Burck) dan Meranti Tembaga (Shorea leprosula Miq) di Kota Palangka Raya : Analysis of Pest and Disease Damage in Balangeran (Shorea balangeran (Korth.) Burck) and Meranti Tembaga (Shorea leprosula Miq) Stands in Palangka Raya City - Firdara, Eritha Kristiana; Penyang, Penyang; Sosilawaty, Sosilawaty; Junaedi, Ajun; Hidayat, Ricky Dwi (HUTAN TROPIKA, 2024)
This study aims to identify diseases and pests, assess the level of stand damage, and compare the level of damage to Balangeran (Shorea balangeran (Korth.) Burck) and Meranti copper (Shorea leprosula Miq) stands on the Green Campus of Palangka Raya University. Sampling was conducted using purposive sampling method with 5% intensity with a total of 150 stands for balangeran and 135 stands for copper meranti. Sampling in the field used a diagonal pattern by taking five sides of each stand plot. The results showed that the dominant pests attacking balangeran and meranti copper stands were green grasshoppers (Oxya chinensis), termites (Coptotermes curvignathus Holmgren), leaf bugs (Pentatomidae), moth caterpillars (Labeda nobilis), bag caterpillars (Metisa plana), for diseases, namely leaf spot (Coletotrichum sp), leaf spot (Pestaliopsis sp), leaf spot (Phomopsis vexans). The frequency of attack and intensity of pest and disease attack from both planting locations showed that the planting area in the nursery for pests was higher than the seed garden area while for diseases in the seed garden area was lower than the nursery area